2005
DOI: 10.1103/physrevd.71.124010
|View full text |Cite
|
Sign up to set email alerts
|

Quasilocal energy-momentum and energy flux at null infinity

Abstract: The null infinity limit of the gravitational energy-momentum and energy flux determined by the covariant Hamiltonian quasi-local expressions is evaluated using the NP spin coefficients. The reference contribution is considered by three different embedding approaches. All of them give the expected Bondi energy and energy flux.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This seeming calamity is actually providential-it is directing us to additional physics contained within the formalism, namely energy flux expressions. 25,85,151 v Sufficient, but not necessary. When examined in detail it can be seen that one really only needs conditions on certain combinations of the components, but it is not in the spirit of our treatment to break fields up into, e.g., components parallel to and perpendicular to some specific boundary surface, etc.…”
Section: Null Infinitymentioning
confidence: 99%
“…This seeming calamity is actually providential-it is directing us to additional physics contained within the formalism, namely energy flux expressions. 25,85,151 v Sufficient, but not necessary. When examined in detail it can be seen that one really only needs conditions on certain combinations of the components, but it is not in the spirit of our treatment to break fields up into, e.g., components parallel to and perpendicular to some specific boundary surface, etc.…”
Section: Null Infinitymentioning
confidence: 99%
“…(11.5), are calculated in [563]. It is shown that, with Minkowski spacetime as a reference configuration, and even with three different embeddings of the two-surface into the reference spacetime, the null infinity limit of these two quantities are just the standard Bondi energy and Bondi mass-loss, respectively.…”
Section: Towards a Full Hamiltonian Approachmentioning
confidence: 99%
“…With the asymptotics (25,26) it is straightforward to verify, as we just stated, that all four of our Hamiltonians are differentiable on the specified phase space-since all the boundary terms in the variations of the Hamiltonians vanish asymptotically; moreover the quasi-local expressions all give the same (since they differ by terms of the form N ∆ϕ∆p which vanish asymptotically) finite constant values (independent of the perturbation α Note that the indicated asymptotic behavior is sufficient but hardly necessary. In practice only the specific projected component combinations that actually show up in the boundary integrand need be so restricted (moreover one need only require this behavior up to a closed form).…”
Section: The Phase Space and Asymptoticsmentioning
confidence: 99%
“…We have reexpressed (57,66) in the asymptotically null regime using the NP spin coefficient formalism and obtained good results [26]. Moreover we are presently working on adapting our expressions to conformal infinity; the results of that investigation will be reported in due course.…”
Section: Application To Einstein's Gravity Theorymentioning
confidence: 99%